Underlying data for the paper "Off-design and Annual Performance Analysis of Supercritical Carbon Dioxide Cycle with Thermal Storage for CSP application " - Thanganadar, Dhinesh; Fornarelli, Francesco; Camporeale, Sergio; Asfand, Faisal; Patchigolla, Kumar (Cranfield University, 2020)
Underlying data for the journal paper "Off-design and Annual Performance Analysis of Supercritical Carbon Dioxide Cycle with Thermal Storage for CSP application "
Keywords: 'Supercritical CO2 cycle'; 'CSP'; 'Annual Performance'; 'Multi-Objective Optimisation'; 'Thermal Energy Storage'; 'Off-design performance'; 'Energy Generation; Conversion and Storage Engineering'